2010
DOI: 10.1111/j.1464-410x.2010.09808.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric magnetic resonance imaging for the detection and localization of prostate cancer: combination of T2‐weighted, dynamic contrast‐enhanced and diffusion‐weighted imaging

Abstract: techniques combined were scored for the likelihood of tumour in each area and results were compared with whole-mount analysis.• The area under the receiver operating characteristic curve ( A z ) was used to evaluate accuracy for tumour detection. The association between MR accuracy and Gleason score was statistically assessed. RESULTS• Of the 456 prostate octants analysed, 145 showed cancer on whole-mount analysis, 120 (83%) of them with a diameter assumed to correspond to a volume > 0.2 cm 3 . Gleason score w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
198
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(213 citation statements)
references
References 31 publications
12
198
3
Order By: Relevance
“…[40] The value of bpMRI in the detection of PCa using 1.5T MRI with endorectal coil has been reported. [23,41] Recently, it has been demonstrated that the sensitivity of bpMRI at 3T without endorectal coil in the detection PCa is similar to that of mpMRI. [20,24,27,28,[42][43][44] The diagnostic value of bpMRI in men with or without prior biopsy and combined with PSA has been validated, resulting in an improved accuracy for detecting clinically significant PCa (sPCa) and representing an effective technique to direct biopsy needles under TRUS guidance, after MRI-ultrasonography fusion.…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%
“…[40] The value of bpMRI in the detection of PCa using 1.5T MRI with endorectal coil has been reported. [23,41] Recently, it has been demonstrated that the sensitivity of bpMRI at 3T without endorectal coil in the detection PCa is similar to that of mpMRI. [20,24,27,28,[42][43][44] The diagnostic value of bpMRI in men with or without prior biopsy and combined with PSA has been validated, resulting in an improved accuracy for detecting clinically significant PCa (sPCa) and representing an effective technique to direct biopsy needles under TRUS guidance, after MRI-ultrasonography fusion.…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%
“…The result is an improvement in specificity from 68% to 87%. As benign prostatic hyperplasia (BPH) is similar to prostate tumour tissue in that they both strongly enhance, it was previously thought that these could be differentiated on DCE-MRI since BPH regions do not wash out as quickly [51,52] and that DCE-MRI could play a role in the identification of transition zone cancers from BPH. This benefit in the transition zone has been refuted in PI-RADS v2.0, and DCE is now only deemed useful in the peripheral zone when DW-MRI has been assigned a score of 3.…”
Section: Dw-mri In Conjunction With Other Mri Acquisition Sequencesmentioning
confidence: 99%
“…Multiparametric prostate imaging was initially implemented on 1.5-Tesla (1.5T) scanners [21][22][23][24][25][26][27][28][29]. To acquire scans with diagnostic value, both a pelvic phased array and an endorectal coil (ERC) were used in combination [30].…”
Section: Hardware and Software Considerationsmentioning
confidence: 99%